Geopolitics of China in Ivory Coast - (:unkn) unknown (My University, 2014)
From Adjamé trader, through the Embassy and finally to the public aid granted by the Chinese government, this thesis analyzes the Sino-African relations by the Ivory Coast’s prism, only allowed scale to highlight the plurality of the Chinese geopolitical issues and the actors integrated into this global China-Africa phenomenon. In Ivory Coast, since the 1983 bilateral recognition and its latent or manifest crisis, these elements are the production of knowledge and the decentralized cooperation (Think Tanks and twinning), institutional support and cooperation projects, trade and investment, relationships, representations, and finally actors and their games of a pragmatic Chinese power who is forging its African experiment through the case of the Ivory Coast.
Keywords: African Research